Pseudopapillary Tumor of Pancreas: a case report - da Silva, Diana Teixeira Ferreira; Moreira, Ricardo Manuel Lopes; Magalhães, Jorge Manuel; Ferreira, Manuel Teixeira; Alpoim e Meneses, José Carlos Machado (Revista Portuguesa de Cirurgia, 2012)
Introduction: Solid pseudopapillary tumors of the pancreas (SPT) is a rare entity, representing about 1-2% of all primary tumors of the pancreas. It affects women in their second or third decade. These tumors have a low malignant potential and prognosis is very good. Methods: Female, 47 years, referred to the emergency department for epigastric pain constant, with 15 days of evolution, associated with anorexia and nausea. Analytical study without changes and abdominal CT revealed “in the body of the pancreas, massive forma- tion of cystic appearance with 9.5 X 4 X 5 cm(...) lobulated, heterogeneous areas with fluid. Cystic mass in appearance but complex”, as confirmed by NMR. Submitted to laparotomic distal pancreactectomy with total splenectomy. Discharged on the 5rd day, with a  good postoperative evolution. Histopathology revealed “neoformation 10cm centrally cavitated, with solid areas in the periphery and hemorrhagic, accounting for pseudopapillary solid tumor of the pancreas, immunohistochemistry positive: cytokeratin AE1/AE3, 8 / 18, vimentin, NSE and progesterone receptors. Discussion: The SPT of the pancreas is a rare tumor. The most common clinical picture is characterized by mass / swelling palpable abdominal and abdominal pain. The diagnosis of PTSD based on factors, clinical and imaging studies. Surgical treatment consists of distal pancreatectomy or pancrea- ticoduodenectomy, laparoscopy or laparotomy. Although surgical resection can be curative, the failure to timely diagnose these tumors may delay proper treatment, thereby increasing mortality. Keywords: solid pseudopapillary pancreatic tumor, diagnosis, surgical treatment, prognosis.